Effect of prenatal Mozart composition on Brain Derived Neurotrophic Factor expression in cerebrum and cerebellum of Rattus norvegicus offspring from Food Restriction 50 model - Yulia Putri Permatasari; Widjiati Widjiati; Hermanto Tri Joewono (Universitas Airlangga, 2018)
Objectives: To analyze the difference of BDNF expression on Rattus norvegicus offspring FR50 model in cerebrum and cerebellum between Mozart composition stimulation group and control.Materials and Methods: An analytical experimental study with single blind randomized post test only control group using animal subjects Rattus norvegicus FR50 model. This study was conducted at animal laboratory, Faculty of Veterinary Medicine, Airlangga University. Animal subjects were divided into Mozart music stimulation group and control. The BDNF expression was analyzed using comparison test, with significancy p<0,05.Results: There was no difference of BDNF expression on Rattus norvegicus offspring FR50 model between Mozart music stimu-lation group and control in cerebrum with p=0.495 (mean Mozart group 6.89+2.52 vs control 6.22+1.99), and cerebellum with p=0.146 (mean Mozart group 7.41+2.67 vs control 5.73+2.45).Conclusions: There was no difference of BDNF expression between Mozart composition stimulation group and control in the cerebrum and cerebellum of Rattus norvegicus offspring FR50 model.